Medical device technologies : a systems based overview using engineering standards - Baura, Gail D. (Academic Press series in biomedical engineering., 2012)
The goal of this textbook is to provide undergraduate engineering students with an introduction to commonly manufactured medical devices. It is the first textbook that discusses both electrical and mechanical medical devices. The first 20 chapters are medical device technology chapters; the remaining 8 chapters are medical device laboratory experiment chapters. Each medical device chapter begins with an exposition of appropriate physiology, mathematical modeling or biocompatibility issues, and clinical need. A device system description and system diagram provide details on technology function.